Proses Berpikir Siswa Kelas XI SMA dalam Menyelesaikan Masalah Barisan dan Deret Aritmatika - Wandini, Rora Rizki; Arisqa, Windi Putri; Ridwan, Fitri Syakira (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
In learning mathematics, critical and logical thinking processes are needed to solve problems correctly, including material about arithmetic sequences and series, which requires good concentration in studying it. This type of research is descriptive qualitative which aims to analyze students' thinking processes in solving problems of arithmetic sequences and series. The subjects in this research were class XI high school students. One of the abilities developed in learning mathematics is the ability to solve problems. Students can do math problems but are not good enough at analyzing and thinking optimally. This causes students' low ability to solve mathematical problems. The research results showed that students were able to work on calculated reasoning cycle questions. Because, in responding to or answering these questions the subject will generally use ideas that have been researched, and the subject can communicate or understand the methods taken to overcome these problems. Some students who use a semi-reasonable reasoning cycle when evaluated in solving problems are not ready to communicate it in their own words. In understanding a problem, students have used these ideas but not enough and students cannot. don't understand the steps to solve this problem. The equation used is correct, but the steps to overcome it are still inappropriate.